#### Answer

$y=(x-2)^{2}+1$

#### Work Step by Step

Given: $y=x^{2}-4x+5$
Step 1: $y=x^{2}-4x+4+1$
Step 2: $y=(x-2)^{2}+1$
Parent graph: $y=x^{2}$
Transformations: Shift on x-axis +2, y-axis +1

Published by
Cengage

ISBN 10:
1285740629

ISBN 13:
978-1-28574-062-1

$y=(x-2)^{2}+1$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.